Lahirnya Pergerakan Perempuan Minangkabau Pada Awal Abad XX - Risa Marta Yati (Kafa`ah: Journal of Gender Studies, 2017)
This article aims to elaborate the influences of the modernization of education that occurred in Minangkabau since the middle of the 19th century to advance of Minangkabau women in the early 20th century. The progress of Minangkabau women is clear in the birth of educated female figures thatwill become to spearhead the emergence of the Minangkabau women's movement. The opening of women’s schools, publication of women's newspapers, the establishment of women's organizations and associations and the active participation in the politics of the national movement are clear proofs of the size of the Minangkabau women's want to appear on the public spaces they never have before.